1990
DOI: 10.1111/j.1471-4159.1990.tb01976.x
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and Regional Studies of the Metabolism of Inositol 1,4,5‐Trisphosphate in Rat Brain

Abstract: Coupling of CNS receptors to phosphoinositide turnover has previously been found to vary with both age and brain region. To determine whether the metabolism of the second messenger inositol 1,4,5-trisphosphate also displays such variations, activities of inositol 1,4,5-trisphosphate 5'-phosphatase and 3'-kinase were measured in developing rat cerebral cortex and adult rat brain regions. The 5'-phosphatase activity was relatively high at birth (approximately 50% of adult values) and increased to adult levels by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
17
1

Year Published

1991
1991
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 34 publications
5
17
1
Order By: Relevance
“…Our present findings regarding the regulation of 3'-kinase activity are in agreement with recent studies using different cell types which reported that the activity of the enzyme is stimulated by physiological concentrations of Ca2 , with an optimal effect elicited at 10-6 M free Ca2+ concentration (22)(23)(24)(25). In this connection, we observed that maximal 3'-kinase activity was significantly increased in the presence of 10-6 M free Ca2+ in both the immature and adult TSM preparations (Fig.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Our present findings regarding the regulation of 3'-kinase activity are in agreement with recent studies using different cell types which reported that the activity of the enzyme is stimulated by physiological concentrations of Ca2 , with an optimal effect elicited at 10-6 M free Ca2+ concentration (22)(23)(24)(25). In this connection, we observed that maximal 3'-kinase activity was significantly increased in the presence of 10-6 M free Ca2+ in both the immature and adult TSM preparations (Fig.…”
Section: Discussionsupporting
confidence: 82%
“…The observed developmental change in 3'-kinase activity is similar to that reported in the maturing rat cerebral cortex, wherein 3'-kinase activity at two weeks ofage was also found to approximate 50% of the adult level (17,22). Moreover, as in the present study, the V. and Km values for 5'-phosphatase in the maturing rat brain were found to significantly exceed the corresponding 3'-kinase determinations (22).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…InsP3 5-phosphatase catalyzes the dephosphorylation of InsPa inactivating the signal. This enzyme is present at high concentration in the brain, particularly in the cerebellum [2,3]. Regulation of this enzyme will directly modify InsPa accumulation and Ca 2+ signalling.…”
Section: Introductionmentioning
confidence: 99%
“…Rat IP3K activity is low at birth and reaches approximately 50% of adult levels [64]. Rat IP3K activities are the highest in the hippocampal CA1 pyramidal neurons, dentate gyrus granule cells, and cerebellar purkinje cells [64,65]. On the other hand, low activities were found in cerebellar granule cells, thalamus, hypothalamus, brainstem, spinal cord, and white matter tracts [64,65].…”
Section: Brain Development Memory and Learningmentioning
confidence: 99%